Postinternationalism and small arms control theory, politics, security - Rogers, Damien 1975- (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2009)
Even though impacts generated by the widespread availability and ongoing use of small arms and light weapons have not reached a magnitude sufficient to radically reorder contemporary world affairs, awareness of the nature and extent of these impacts has compelled some international actors to take decisive action. Damien Rogers examines how the international community has responded to the challenge of controlling small arms and light weapons since the early 1990s. Using a postinternationalist analytic framework, he specifically focuses on the maturing relationships between particular actors of world affairs and the nascent interconnectivity between their strategies for, and approaches toward, controlling these weapons. Furthermore, the book identifies ways in which the captains of small arms industry, arms brokers and chief users of these weapons are able to mitigate, resist or elude the intended effects of those responses